Superior Mesenteric Artery Syndrome as an Atypical Aetiology of Upper Intestinal Obstruction in a Young Adult - CHEONG, KANG WEI; Chandran Nadarajan (The Interventionalist Journal, 2023)
Superior mesenteric artery (SMA) syndrome is an uncommon cause of proximal intestinal obstruction in young adults. Weight loss is one of the most significant aetiology of this condition. In young patients presenting with post-prandial abdominal pain, abdominal distension, nausea, anorexia and voluminous vomiting, the diagnosis of superior mesenteric artery syndrome should be considered. These symptoms are due to compression of the third part of the duodenum against the aorta by the overlying superior mesenteric artery. Computed tomography (CT) angiography of the abdomen is currently favoured in the literature to establish the diagnosis. We report a case of SMA syndrome in a 20-year-old Malay gentleman with a history of significant weight loss and kratom abuse for a year. A CT scan of the abdomen was performed and established the diagnosis. This patient responded to conservative treatment of nutritional supplementation.